2014
DOI: 10.1007/s10549-014-3037-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-221/222 enhances tamoxifen resistance in recipient ER-positive breast cancer cells

Abstract: Recent studies have demonstrated that specific miRNAs, such as miR-221/222, may be responsible for tamoxifen resistance in breast cancer. Secreted miRNAs enclosed in exosomes can act as intercellular bio-messengers. Our objective is to investigate the role of secreted miR-221/222 in tamoxifen resistance of ER-positive breast cancer cells. Transmission electron microscopy analysis and nanoparticle tracking analysis were performed to determine the exosomes difference between MCF-7(TamR) (tamoxifen resistant) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
226
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(230 citation statements)
references
References 40 publications
3
226
0
1
Order By: Relevance
“…MiR-221/222 are negative regulators of p27 kip1 , a cell cycle inhibitor and tumor suppressor, [46][47][48][49][50] and upregulated expressions of these miRNAs and significant reductions in p27 kip1 levels have been reported in tamoxifen-resistant breast cancer cells; therefore, miR-221/222 might regulate tamoxifen sensitivity via the direct targeting of p27 kip1 . 51,52 Pichiorri et al 53 found that miR-221/222 expressions were modulated by nucleolin at the post-transcriptional level. Recently, it has been indicated that these miRNAs induce resistance to the selective ER downregulator, and this was caused by the activation of β-catenin and the repression of transforming growth factor-β-mediated growth inhibition.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…MiR-221/222 are negative regulators of p27 kip1 , a cell cycle inhibitor and tumor suppressor, [46][47][48][49][50] and upregulated expressions of these miRNAs and significant reductions in p27 kip1 levels have been reported in tamoxifen-resistant breast cancer cells; therefore, miR-221/222 might regulate tamoxifen sensitivity via the direct targeting of p27 kip1 . 51,52 Pichiorri et al 53 found that miR-221/222 expressions were modulated by nucleolin at the post-transcriptional level. Recently, it has been indicated that these miRNAs induce resistance to the selective ER downregulator, and this was caused by the activation of β-catenin and the repression of transforming growth factor-β-mediated growth inhibition.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…In relation to tamoxifen, exosomes from tamoxifen-resistant MCF-7 cells were found to promote proliferation of MCF-7 wild-type cells. Functional assays (cell viability, apoptosis, and colony formation) assessed the involvement of miR-221 and miR-222 in the transfer of this tamoxifen resistance, which was found to be significantly blocked using anti-miR-221/anti-miR-222 (66 ).…”
Section: Drug Resistancementioning
confidence: 99%
“…Reports in the recent years have indicated the involvement of miRNAs in tamoxifen resistance as well. Specifically, miR-221/222 enhanced tamoxifen resistance in recipient cells by reducing the target genes expression of P27 and Era [16]. MiR-148a and miR-152 were able to reduce tamoxifen resistance in ER-positive breast cancer via downregulating ALCAM [10].…”
Section: Introductionmentioning
confidence: 96%